Positive pole piece, electrochemical device and electronic device
By providing a dense first coating on the positive electrode sheet of the lithium-ion battery, the problem of short circuit in the lithium-ion battery during the nailing process is solved, and its safety performance and cycling performance are improved.
Patent Information
- Application Number
- CN202510034217.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
Existing lithium-ion batteries are prone to internal short circuits during the nailing process, affecting their safety performance and cycling performance.
A first coating layer including inorganic particles and a first binder is provided on the surface of the positive electrode current collector of the positive electrode sheet, and the thickness of the Dv50 of the inorganic particles and the first coating is regulated to form a dense first coating layer, enhance protection of the positive electrode current collector and reduce the occurrence of internal short circuits.
By increasing the bulk density between the inorganic particles, a dense first coating is formed, which effectively reduces the occurrence of internal short circuits, reduces the probability of local overheating, and improves the safety and cycling performance of the electrochemical device.
Smart Images

Figure CN119833560A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode sheet, an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices (such as lithium-ion batteries) have entered our daily lives with the advancement of technology and the improvement of environmental protection requirements. With the widespread popularity of lithium-ion batteries, their cycle performance has been increasingly valued by users, and consumers, after-sales service providers and manufacturers have also put forward new requirements for the safety performance of lithium-ion batteries.
[0003] However, the current technology to improve the safety performance of lithium-ion batteries is not mature. During use, the positive and negative pole pieces of lithium-ion batteries often come into contact with each other during the nailing process, or the positive and negative pole pieces are connected by nails, which leads to internal short circuits, affecting the safety performance of lithium-ion batteries and reducing the cycle performance. Therefore, the market is in urgent need of a lithium-ion battery with good safety and cycle performance. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode plate, an electrochemical device and an electronic device to improve the safety performance and cycle performance of the electrochemical device.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides a positive electrode plate, the positive electrode plate includes a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode current collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode current collector, the first coating includes inorganic particles and a first binder, the Dv50 of the inorganic particles is 50nm to 500nm, preferably 50nm to 200nm; the thickness of the first coating is 0.2μm to 2μm, preferably 0.2μm to 0.95μm. The present application can increase the packing density between the inorganic particles by arranging the first coating on the positive electrode plate and regulating the Dv50 of the inorganic particles and the thickness of the first coating within the scope of the present application, form a relatively dense first coating on the surface of the positive electrode current collector, enhance the protection of the positive electrode current collector during the nail penetration test, wrap the metal burrs that may be generated by the positive electrode current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, and reduce the probability of thermal runaway caused by local overheating of the electrochemical device, thereby improving the safety performance and cycle performance of the electrochemical device.
[0007] In one embodiment of the present application, the Dv90 of the inorganic particles is 400nm to 800nm. When the Dv90 of the inorganic particles is within the range of the present application, the inorganic particles with nanometer particle size are conducive to increasing the packing density between the inorganic particles, forming a relatively dense first coating on the surface of the positive electrode current collector, and enhancing the protection of the positive electrode current collector during the nail penetration test, thereby helping to improve the safety performance of the electrochemical device.
[0008] In one embodiment of the present application, the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is 35 to 450. When the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is within the range of the present application, the energy density of the electrochemical device is high while also having good safety performance and cycle performance.
[0009] In one embodiment of the present application, the inorganic particles include at least one of nanoboehmite or aluminum oxide; based on the mass of the first coating, the mass percentage of the inorganic particles is 80% to 89.5%. When the inorganic particles are selected from the above materials and the mass percentage is within the scope of the present application, the first coating has a higher diaphragm resistance, which can increase the short-circuit resistance of the electrochemical device when a short circuit occurs, reduce the dangerous short-circuit point between the positive electrode and the negative electrode during the nailing process, and reduce the heat generation power during the short circuit, thereby helping to improve the safety performance of the electrochemical device. At the same time, when the inorganic particles are selected from the above materials and the mass percentage is within the scope of the present application, the first coating has a higher diaphragm resistance, so that the thickness of the first coating can be made thinner, such as 0.2μm to 2μm, or even 0.2μm to 0.95μm, thereby improving the safety characteristics of the electrochemical device and the energy density of the electrochemical device.
[0010] In one embodiment of the present application, the first binder includes at least one of aluminum dihydrogen phosphate, potassium dihydrogen phosphate or sodium dihydrogen phosphate; based on the mass of the first coating, the mass percentage of the first binder is 5% to 10%. When the first binder is selected from the above materials and the mass percentage is within the scope of the present application, the bonding force between the first coating and the positive electrode current collector can be improved, the degree of peeling between the first coating and the positive electrode current collector during the cycle process can be reduced, and the interface contact impedance during the cycle process can be improved, thereby facilitating the improvement of the cycle performance of the electrochemical device.
[0011] In one embodiment of the present application, the glass transition temperature (T g ) is 90° C. to 180° C. When the glass transition temperature of the first binder is within the range of the present application, the overall adhesion of the first coating layer can be increased, and the adhesion between the first coating layer and the positive electrode current collector can be improved, thereby facilitating the improvement of the safety performance and cycle performance of the electrochemical device.
[0012] In one embodiment of the present application, the bonding force between the first coating and the positive electrode current collector is 600 N / m to 2000 N / m. When the bonding force between the first coating and the positive electrode current collector is within the scope of the present application, it indicates that the first coating and the positive electrode current collector have good bonding, which is beneficial to improving the safety performance and cycle performance of the electrochemical device.
[0013] In one embodiment of the present application, the first coating layer also includes a second binder, and the second binder includes a water-soluble metal salt compound; based on the mass of the first coating layer, the mass percentage of the second binder is 5% to 10%. When the second binder is selected from the above materials and the mass percentage is within the scope of the present application, the water-soluble metal salt compound has good hydrophilicity, which is beneficial to the transmission of electrons and ions in the positive electrode sheet, improves the kinetic performance of the electrochemical device, and improves the cycle performance of the electrochemical device; the water-soluble metal salt compound is used as a binder in the first coating layer, which can improve the tensile strength of the first coating layer. At the same time, the water-soluble metal salt compound has many polar functional groups and has a strong interaction with the positive current collector, which is beneficial to improve the bonding force between the first coating layer and the positive current collector, and improve the safety performance of the electrochemical device.
[0014] In one embodiment of the present application, the water-soluble metal salt compound includes an alkali metal polyacrylate and / or an alkaline earth metal polyacrylate, the alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate, and the alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate. When the water-soluble metal salt compound is selected from the above materials, it has good hydrophilicity, which is beneficial to the transmission of electrons and ions in the positive electrode plate, improves the kinetic performance of the electrochemical device, and further improves the cycle performance of the electrochemical device; the above water-soluble metal salt compound is used as a binder in the first coating, which can further improve the tensile strength of the first coating. At the same time, the water-soluble metal salt compound has many polar functional groups and has a strong interaction with the positive current collector, which is beneficial to improve the bonding force between the first coating and the positive current collector, and further improves the safety performance of the electrochemical device.
[0015] In one embodiment of the present application, the first coating layer further includes a first conductive agent, and the first conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene or carbon nanofibers; based on the mass of the first coating layer, the mass percentage of the first conductive agent is 0.5% to 5%. When the first conductive agent is selected from the above materials and the mass percentage is within the range of the present application, the first coating layer has a high short-circuit resistance and good conductivity, which is beneficial to improving the cycle performance of the electrochemical device.
[0016] In one embodiment of the present application, the infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm-1 There are characteristic peaks between them. 3200cm in infrared spectrum -1 Up to 3400cm -1 It is the characteristic peak position of the hydroxyl functional group on the surface of the inorganic particle. When the infrared spectrum of the first coating has this characteristic peak, the hydroxyl functional group on the surface of the inorganic particle can be connected with the carboxylic acid group contained in the second binder through hydrogen bonds, thereby increasing the cohesion of the first coating and the bonding force between the first coating and the positive electrode collector, which is beneficial to improving the safety performance of the electrochemical device.
[0017] In one embodiment of the present application, the membrane resistance of the first coating is R1, the membrane resistance of the positive electrode is R2, 5Ω≤R1≤200Ω, 0.5Ω≤R2≤7Ω. When the values of R1 and R2 are within the range of the present application, the electrochemical device has good safety performance and cycle performance.
[0018] The second aspect of the present application provides an electrochemical device, the electrochemical device comprising the positive electrode sheet in any of the above embodiments. The electrochemical device of the present application has good safety performance and cycle performance.
[0019] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has a long service life and good performance.
[0020] Beneficial effects of this application:
[0021] The present application provides a positive electrode sheet, an electrochemical device and an electronic device. The positive electrode sheet includes a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode current collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode current collector, the first coating includes inorganic particles and a first binder, the Dv50 of the inorganic particles is 50nm to 500nm, and the thickness of the first coating is 0.2μm to 2μm. The present application can increase the packing density between the inorganic particles by arranging the first coating on the positive electrode sheet and regulating the Dv50 of the inorganic particles and the thickness of the first coating within the scope of the present application, forming a relatively dense first coating on the surface of the positive electrode current collector, enhancing the protective effect on the positive electrode current collector during the nail penetration test, wrapping the metal burrs that may be generated by the positive electrode current collector during the nail penetration test, reducing the occurrence of short circuits in the electrochemical device, and reducing the probability of thermal runaway caused by local overheating of the electrochemical device, thereby improving the safety performance and cycle performance of the electrochemical device.
[0022] Of course, implementing any product or method of the present application does not necessarily require achieving all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0024] Figure 1 A schematic diagram of the structure of a positive electrode sheet along its thickness direction according to an embodiment of the present application;
[0025] Figure 2 This is an infrared spectrum test chart of the first coating layer of Example 1 of the present application;
[0026] Figure 3 This is an infrared spectrum test chart of the first coating of Example 24 of the present application.
[0027] Reference numerals: 11 - positive electrode current collector; 12 - first coating layer; 13 - positive electrode material layer. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0029] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0030] The first aspect of the present application provides a positive electrode plate, the positive electrode plate comprises a positive current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive current collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive current collector. The first coating comprises inorganic particles and a first binder, the Dv50 of the inorganic particles is 50nm to 500nm, preferably 50nm to 200nm; the thickness of the first coating is 0.2μm to 2μm, preferably 0.2μm to 0.95μm. For example, the Dv50 of the inorganic particles can be 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or a range consisting of any two of the values therein; the thickness of the first coating can be 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 0.95μm, 1μm, 1.5μm, 2μm or a range consisting of any two of the values therein.
[0031] The positive electrode sheet of the present application is provided with a first coating, which can reduce the short-circuit points caused by contact between the positive electrode sheet and the negative electrode sheet in the nail penetration test, increase the short-circuit resistance when the electrochemical device is short-circuited, and reduce the heat generation power during the short circuit. In addition, due to the phase change of the positive active material, the volume of the positive electrode material layer will increase during the cycle, and the first coating with strong adhesion can alleviate the deformation of the positive current collector during the cycle, improve the contact between the positive current collector and the first coating and the positive electrode material layer, and promote the transmission of electrons in the positive electrode sheet, thereby improving the safety performance and cycle performance of the electrochemical device. The first coating includes a first binder, which can also improve the adhesion between the first coating and the positive current collector, reduce the degree of peeling between the first coating and the positive current collector during the cycle, reduce the interface contact impedance during the cycle, and improve the cycle performance of the electrochemical device.
[0032] When the first coating includes inorganic particles and the Dv50 of the inorganic particles is regulated within the scope of the present application, the inorganic particles with nanometer particle size can increase the packing density between the inorganic particles, form a relatively dense first coating on the surface of the positive electrode collector, improve the cohesion of the first coating, enhance the protection of the positive electrode collector during the nail penetration test, wrap the metal burrs that may be generated by the positive electrode collector in the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, reduce the side reactions between the positive electrode plate and the electrolyte, and improve the safety performance and cycle performance of the electrochemical device. When the Dv50 of the inorganic particles is greater than 500nm, the inorganic particles with too large particle size can easily puncture the positive electrode current collector during the nail penetration test, and the protection effect on the positive electrode current collector is poor, affecting the safety performance of the electrochemical device; when the Dv50 of the inorganic particles is less than 50nm, the preparation process of the inorganic particles is more difficult and the preparation cost is higher. The probability of agglomeration in the first coating slurry is also increased, affecting the uniformity of the first coating. At the same time, there are more side reactions between the positive electrode plate and the electrolyte, resulting in a decrease in the cycle performance of the electrochemical device.
[0033] When the thickness of the first coating is regulated within the scope of this application, the first coating has a high mechanical strength, can protect the positive electrode current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the safety performance of the electrochemical device. When the thickness of the first coating is less than 0.2μm, the protection effect on the positive electrode current collector is poor, affecting the safety performance of the electrochemical device; when the thickness of the first coating is greater than 2μm, the volume energy density of the electrochemical device is low, and the resistance of the positive electrode plate is large, which affects the transmission of electrons in the positive electrode plate, thereby causing a decrease in the cycle performance of the electrochemical device.
[0034] Therefore, the present application sets a first coating on the positive electrode plate and regulates the Dv50 of the inorganic particles and the thickness of the first coating within the scope of the present application, so as to form a relatively dense and mechanically strong first coating on the surface of the positive electrode collector, thereby improving the safety performance and cycle performance of the electrochemical device.
[0035] In this application, the above-mentioned “the first coating is disposed on the surface of the positive electrode current collector” means that the first coating can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of the positive electrode current collector, or it can be a partial area of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. Specifically, if Figure 1 As shown, a first coating layer 12 and a positive electrode material layer 13 are sequentially stacked on the two surfaces of the positive electrode current collector 11. The above-mentioned "the positive electrode material layer is arranged on the surface of the first coating layer away from the positive electrode current collector" can be understood by analogy, and the positive electrode material layer can be arranged in the entire area of the first coating layer, and can also be arranged in a partial area of the first coating layer.
[0036] In one embodiment of the present application, the Dv90 of the inorganic particles is 400nm to 800nm. For example, the Dv90 of the inorganic particles can be 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm or a range consisting of any two of the values. When the Dv90 of the inorganic particles is within the scope of the present application, the inorganic particles of nanometer particle size can increase the packing density between the inorganic particles, form a denser first coating on the surface of the positive electrode collector, enhance the protection of the positive electrode collector during the nail penetration test, wrap the metal burrs that may be generated by the positive electrode collector in the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, and reduce the probability of thermal runaway caused by local overheating of the electrochemical device, thereby helping to improve the safety performance of the electrochemical device.
[0037] In one embodiment of the present application, the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is 35 to 450. For example, the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer can be 35, 50, 60, 65, 73, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450 or a range consisting of any two of the values. When the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is within the scope of the present application, the energy density of the electrochemical device is high, and it also has good safety performance and cycle performance. In the present application, the thickness of the positive electrode material layer refers to the thickness of the single-sided positive electrode material layer, and the thickness of the first coating layer refers to the thickness of the single-sided first coating layer.
[0038] In one embodiment of the present application, the thickness of the positive electrode material layer is 70 μm to 90 μm. For example, the thickness of the positive electrode material layer can be 70 μm, 72 μm, 75 μm, 78 μm, 80 μm, 83 μm, 85 μm, 88 μm, 90 μm, or a range consisting of any two of these values.
[0039] In one embodiment of the present application, the inorganic particles include at least one of nano-boehmite or aluminum oxide (Al2O3); based on the mass of the first coating, the mass percentage of the inorganic particles is 80% to 89.5%. For example, the mass percentage of the inorganic particles can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 89.5% or a range consisting of any two of these values. When the inorganic particles are selected from the above materials and the mass percentage is within the scope of the present application, the first coating has a higher diaphragm resistance, which can increase the short-circuit resistance of the electrochemical device when a short circuit occurs, reduce the dangerous short-circuit point between the positive electrode sheet and the negative electrode sheet during the nailing process, and reduce the heat generation power during the short circuit, thereby helping to improve the safety performance of the electrochemical device. At the same time, when the inorganic particles are selected from the above materials and the mass percentage is within the range of this application, the first coating has a higher membrane resistance. In this way, the thickness of the first coating can be made thinner, such as 0.2μm to 2μm, or even 0.2μm to 0.95μm, thereby improving the safety characteristics of the electrochemical device while increasing the energy density of the electrochemical device.
[0040] In one embodiment of the present application, the first binder includes at least one of aluminum dihydrogen phosphate, potassium dihydrogen phosphate or sodium dihydrogen phosphate; based on the mass of the first coating, the mass percentage of the first binder is 5% to 10%. For example, the mass percentage of the first binder can be 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of these values. When the first binder is selected from the above materials and the mass percentage is within the scope of the present application, the bonding force between the first coating and the positive current collector can be improved, the degree of peeling between the first coating and the positive current collector during the cycle can be reduced, and the interface contact impedance during the cycle can be reduced, thereby helping to improve the cycle performance of the electrochemical device.
[0041] In one embodiment of the present application, the glass transition temperature of the first binder is 90°C to 180°C. For example, the glass transition temperature of the first binder can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, or a range consisting of any two of these values. When the glass transition temperature of the first binder is within the range of the present application, the adhesion of the first coating as a whole can be increased, and the adhesion between the first coating and the positive electrode current collector can be increased, thereby facilitating the improvement of the safety performance and cycle performance of the electrochemical device.
[0042] In one embodiment of the present application, the bonding force between the first coating and the positive electrode current collector is 600N / m to 2000N / m. For example, the bonding force between the first coating and the positive electrode current collector can be 600N / m, 800N / m, 1000N / m, 1200N / m, 1400N / m, 1600N / m, 1800N / m, 2000N / m or a range consisting of any two of these values. When the bonding force between the first coating and the positive electrode current collector is within the scope of the present application, it means that the first coating and the positive electrode current collector have good bonding, and the first coating can wrap the metal burrs that may be generated in the positive electrode current collector under abnormal conditions such as nail penetration and impact, so as to reduce the occurrence of short circuits in the electrochemical device. At the same time, the probability of thermal runaway or overheating of the electrochemical device due to local overheating can be reduced, and the safety performance of the electrochemical device can be improved. On the other hand, since the volume of the positive electrode active material in the positive electrode material layer will expand during the cycle, the first coating layer with strong adhesion can alleviate the deformation of the positive electrode current collector during the cycle, improve the contact between the positive electrode current collector and the first coating layer and the positive electrode material layer, which is beneficial to the transmission of electrons in the positive electrode sheet, thereby improving the cycle performance of the electrochemical device.
[0043] In one embodiment of the present application, the first coating layer further includes a second binder, and the second binder includes a water-soluble metal salt compound; based on the mass of the first coating layer, the mass percentage of the second binder is 5% to 10%. For example, the mass percentage of the second binder can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or a range consisting of any two of these values. When the second binder is selected from the above materials and the mass percentage is within the scope of this application, the water-soluble metal salt compound has good hydrophilicity, which is beneficial to the transmission of electrons and ions in the positive electrode sheet, and the electronic conductivity and ionic conductivity are better than those of non-water-soluble polymers such as polyvinylidene fluoride and polyvinylidene chloride. Therefore, applying it to the first coating can improve the kinetic performance of the electrochemical device and improve the cycle performance of the electrochemical device; in addition, the water-soluble metal salt compound has a large specific surface area and can be highly dispersed after contacting water. When used as a binder in the first coating, the tensile strength of the first coating can be improved. At the same time, the water-soluble metal salt compound has many polar functional groups (for example, carboxyl -COOH), and the above polar functional groups can form hydrogen bonds or covalent bonds with the hydroxyl groups (-OH) on the surface of the inorganic particles. Under certain conditions, ester bonds can also be formed through dehydration reaction, and interact with the positive current collector, which is beneficial to improve the bonding force between the first coating and the positive current collector and the cohesive force of the first coating, thereby improving the safety performance of the electrochemical device.
[0044] In one embodiment of the present application, the water-soluble metal salt compound includes an alkali metal salt of polyacrylic acid and / or an alkaline earth metal salt of polyacrylic acid, the alkali metal salt of polyacrylic acid includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate, and the alkaline earth metal salt of polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate. When the water-soluble metal salt compound is selected from the above materials, the hydrophilicity is good, which is conducive to the transmission of electrons and ions in the positive electrode sheet, and the electronic conductivity and ionic conductivity are better than those of non-water-soluble polymers such as polyvinylidene fluoride and polyvinylidene chloride. Therefore, applying it to the first coating can improve the kinetic performance of the electrochemical device and further improve the cycle performance of the electrochemical device; in addition, the above water-soluble metal salt compound has a large specific surface area and can be highly dispersed after contacting water. It is applied to the first coating as a binder, which can further improve the tensile strength of the first coating. At the same time, the above water-soluble metal salt compound has many polar functional groups and strong interaction with the positive current collector, which is conducive to improving the bonding force between the first coating and the positive current collector and the cohesive force of the first coating, and further improving the safety performance of the electrochemical device.
[0045] In one embodiment of the present application, the first coating layer further includes a first conductive agent, and the first conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene or carbon nanofibers; based on the mass of the first coating layer, the mass percentage of the first conductive agent is 0.5% to 5%. For example, the mass percentage of the first conductive agent can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of the values. When the first conductive agent is selected from the above materials and the mass percentage is within the scope of the present application, it is beneficial to form a uniform conductive network between the positive electrode material layer and the positive electrode current collector, improve the transmission of electrons in the positive electrode sheet, and make the first coating layer have good conductivity while having a high short-circuit resistance, thereby helping to improve the cycle performance of the electrochemical device.
[0046] In one embodiment of the present application, the infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 There are characteristic peaks between them. 3200cm in infrared spectrum -1 Up to 3400cm -1 It is the characteristic peak position of the hydroxyl functional group on the surface of the inorganic particle. When the infrared spectrum of the first coating has this characteristic peak, the hydroxyl functional group on the surface of the inorganic particle can be connected with the carboxylic acid group contained in the second binder through hydrogen bonds, thereby increasing the cohesion of the first coating and the bonding force between the first coating and the positive electrode collector, which is beneficial to improving the safety performance of the electrochemical device.
[0047] In some embodiments, the hydroxyl functional groups on the surface of the inorganic particles can be obtained by treating the inorganic particles with a silane coupling agent (e.g., 3-aminopropyltriethoxysilane (APTES), 3-glycidyloxypropyltrimethoxysilane (GPTS)). In other embodiments, the inorganic particles containing hydroxyl functional groups can be purchased, and the inorganic particles can be tested in combination with the "infrared spectroscopy test" test method to select the desired inorganic particles.
[0048] In one embodiment of the present application, the diaphragm resistance of the first coating is R1, and the diaphragm resistance of the positive electrode is R2, 5Ω≤R1≤200Ω, 0.5Ω≤R2≤7Ω. For example, R1 can be 5Ω, 20Ω, 50Ω, 80Ω, 100Ω, 120Ω, 150Ω, 170Ω, 200Ω, or a range consisting of any two of these values; R2 can be 0.5Ω, 0.8Ω, 1Ω, 1.5Ω, 2Ω, 2.5Ω, 3Ω, 3.5Ω, 4Ω, 5Ω, 6Ω, 7Ω, or a range consisting of any two of these values. When the value of R1 is within the range of the present application, it can reduce the short-circuit points caused by contact between the positive electrode and the negative electrode in the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the safety performance of the electrochemical device. When the value of R2 is within the range of the present application, the transmission rate of electrons in the positive electrode plate is high, and the electrochemical device has good safety performance and cycle performance.
[0049] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation of the positive electrode sheet may include but is not limited to the following steps: the inorganic particles, the first binder and the first conductive agent are mixed in a mass ratio of (85 to 89.5): (5.5 to 10): (0.5 to 5), deionized water is added as a solvent, and the first coating slurry with a solid content of 70wt% to 80wt% is obtained; or, the inorganic particles, the first binder, the second binder and the first conductive agent are mixed in a mass ratio of (80 to 89.5): (5 to 10): (5 to 10): (0.5 to 5), deionized water is added as a solvent, and the first coating slurry with a solid content of 70wt% to 80wt% is obtained. Then the first coating slurry is coated on one surface of the positive electrode current collector of 5μm to 20μm, and the first coating with a thickness of 0.2μm to 2μm is obtained after baking at 90℃ to 180℃ for 1h to 3h. Then, a positive electrode material layer slurry is prepared, and the positive electrode material layer slurry is coated on the surface of the first coating layer, and dried to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on one side. The above steps are repeated on the other surface of the positive electrode current collector to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on both sides.
[0050] When preparing the first coating, the first binder baked at 90°C to 180°C can increase the cohesion of the first coating and the bonding force between the first coating and the positive electrode current collector after being triggered by high temperature. The reason is that, on the one hand, under the action of high temperature, the first binder (for example, aluminum dihydrogen phosphate) will undergo a dehydration reaction to generate a more stable compound (for example, aluminum phosphate AlPO4), and the water molecules generated in the above reaction process can promote the first binder to react with the hydroxyl groups on the surface of the positive electrode current collector to form a stable chemical bond; on the other hand, there is usually an oxide layer on the surface of the positive electrode current collector (for example, there is an aluminum oxide layer for aluminum foil), and under the action of high temperature, the first binder (for example, aluminum dihydrogen phosphate) can react with the above oxide to generate a more stable compound (for example, aluminum dihydrogen phosphate), thereby increasing the cohesion of the first coating and the bonding force between the first coating and the positive electrode current collector.
[0051] In the present application, Dv50 represents the particle size at which the volume accumulation reaches 50% from the small particle size side in the volume-based particle size distribution of inorganic particles; Dv90 represents the particle size at which the volume accumulation reaches 90% from the small particle size side in the volume-based particle size distribution of inorganic particles.
[0052] Generally, inorganic particles of different particle sizes can be obtained by mechanical crushing (such as ball milling). For example, the particle size of inorganic particles can be controlled by adjusting the ball milling time. When other conditions remain unchanged, the Dv50 and Dv90 of inorganic particles decrease with the extension of ball milling time; and the Dv50 and Dv90 of inorganic particles increase with the shortening of ball milling time.
[0053] Generally, the thickness of the first coating layer can be regulated by regulating the single-sided coating weight of the first coating layer. For example, when other conditions remain unchanged, the single-sided coating weight of the first coating layer increases, and the thickness of the first coating layer increases; and the single-sided coating weight of the first coating layer decreases, and the thickness of the first coating layer decreases.
[0054] In the present application, the inorganic particles of different particle sizes and the first binder of different glass transition temperatures can be purchased, and the particle size of the inorganic particles can be tested by the "particle size test" test method provided in the present application, and the glass transition temperature of the first binder can be tested by the "glass transition temperature test" test method provided in the present application, and the inorganic particles of the required particle size and the first binder of the required glass transition temperature can be selected.
[0055] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0056] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0057] The positive electrode material layer may also include a second conductive agent and a third binder. The present application does not particularly limit the types of the second conductive agent and the third binder, as long as the purpose of the present application can be achieved. For example, the second conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the third binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the second conductive agent, and the third binder in the positive electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.
[0058] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 10 μm.
[0059] The second aspect of the present application provides an electrochemical device, which includes the positive electrode plate in any of the aforementioned embodiments. The electrochemical device also includes a negative electrode plate, which includes a negative electrode collector and a negative electrode material layer disposed on at least one surface of the negative electrode collector. The above-mentioned "negative electrode plate includes a negative electrode collector and a negative electrode material layer disposed on at least one surface of the negative electrode collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode collector along the thickness direction of itself, or on two surfaces of the negative electrode collector along the thickness direction of itself. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode collector, or it can be a partial area of the surface of the negative electrode collector. This application is not particularly limited as long as the purpose of this application can be achieved.
[0060] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector or a titanium-copper composite current collector, etc.
[0061] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0062] In some embodiments of the present application, the negative electrode material layer may further include a third conductive agent and a fourth binder, for example, at least one of the second conductive agent and the third binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the third conductive agent, and the fourth binder in the negative electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0063] The present application has no particular limitation on the thickness of the negative electrode material layer and the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 80 μm to 100 μm, and the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0064] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive layer conductive agent and a conductive layer binder. The present application has no particular restrictions on the conductive layer conductive agent and the conductive layer binder in the conductive layer, which may be, for example, at least one of the above-mentioned second conductive agent and the above-mentioned third binder.
[0065] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) membranes), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0066] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0067] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0068] In some embodiments of the present application, the inorganic layer includes ceramic particles and an inorganic layer binder. The present application has no particular restrictions on ceramic particles, such as ceramic particles can include at least one of silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the inorganic layer binder, such as the inorganic layer binder can be at least one of the third binder mentioned above. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0069] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0070] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0071] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.
[0072] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0073] The carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0074] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0075] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0076] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has a long service life and good performance.
[0077] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0078] Example
[0079] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0080] Test methods and equipment:
[0081] Particle size testing
[0082] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the positive electrode sheet, and the positive electrode sheet was cleaned with dimethyl carbonate (DMC) for 10 minutes, and then the positive electrode sheet was baked at 100°C for 2 hours for standby use. The positive electrode material layer on the positive electrode sheet was scraped off to obtain a positive electrode current collector with a first coating on the surface, and then the first coating was scraped off with a scraper to obtain the first coating powder. The first coating powder was treated at 500°C in air for 4 hours, and the inorganic particles were calcined and separated. The particle size Dv50 and Dv90 of the inorganic particles were tested using a Malvern particle size tester (model MasterSizer 2000). Among them, the specific test was carried out in accordance with the national standard GB / T19077-2016 "Laser Diffraction Method for Particle Size Distribution".
[0083] Thickness test
[0084] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the positive electrode sheet. The positive electrode sheet was cleaned with dimethyl carbonate (DMC) for 10 minutes, and then the positive electrode sheet was baked at 100°C for 2 hours for standby use. The positive electrode sheet was cut and the cross section of the positive electrode sheet along the thickness direction was polished with argon ions. Then, a scanning electron microscope (OXFORD·EDS) was used to observe and measure the thickness of the first coating at three locations, and the average value was the thickness of the first coating. The thickness of the positive electrode material layer was observed and measured at three locations, and the average value was the thickness of the positive electrode material layer.
[0085] Cyclic performance test
[0086] After the lithium-ion battery is left to stand for 30 minutes in an environment of 45℃±3℃, it is charged to 4.25V at a constant current of 1.25C, then charged to 4.5V at a constant current of 1.5C, then charged to 0.05C at a constant voltage of 4.5V, left to stand for 30 minutes, and then discharged to 3.0V at a constant current of 0.7C. The discharge capacity obtained in this step is the initial capacity. Repeat the above cycle, and the discharge capacity of each cycle is compared with the initial capacity to obtain the discharge capacity retention rate of each cycle, and record the number of cycles of the lithium-ion battery at 45℃±3℃ until the discharge capacity retention rate is 80%. The number of cycles at 45℃±3℃ until the capacity retention rate is 80% is recorded as the cycle performance of the lithium-ion battery. The higher the number of cycles at 45℃±3℃ until the capacity retention rate is 80%, the better the cycle performance of the lithium-ion battery.
[0087] Nail penetration test
[0088] Take 10 lithium-ion batteries in each embodiment and comparative example, and fully charge them at 25±3°C. The specific steps are: charge at a constant current of 0.5C to 4.5V, and then charge at a constant voltage of 4.5V to a current cutoff of 0.05C.
[0089] The lithium-ion battery was subjected to a nail penetration test at 25±3℃, using a steel nail with a diameter of 4mm, made of carbon steel, with a taper of 16.5mm, and a total length of 100mm. The nail penetration speed was set to 30mm / s, and the nail penetration depth was based on the taper of the steel nail passing through the lithium-ion battery. The state of the lithium-ion battery was observed during the test, and the lithium-ion battery was judged as passing the nail penetration test based on the criterion of not burning or exploding. The number of lithium-ion batteries that passed the nail penetration test was recorded. The safety performance of lithium-ion batteries is characterized by the pass rate of the nail penetration test. The higher the pass rate of the nail penetration test, the better the safety performance of the lithium-ion battery.
[0090] Glass transition temperature test
[0091] Take 5 mg of the first binder sample and place it in the crucible of the differential scanning calorimeter (DSC). Set the experimental parameters, including the starting temperature of 25°C, the ending temperature of 500°C, and the heating rate of 5°C / min, and start the equipment to start the test. The differential scanning calorimeter records the change of the heat flow difference between the sample and the reference as the temperature or time changes. After the test is completed, a DSC curve is generated, and the temperature corresponding to the step change of the baseline of the DSC curve is recorded. This temperature is the glass transition temperature of the first binder.
[0092] Adhesion test
[0093] Take the positive electrode sheet coated only with the first coating, stick the positive electrode sheet on a smooth steel plate with double-sided tape, stick the other side of the positive electrode sheet with tape, and fix one end of the tape on the tensile testing machine. Set the speed to 10 mm / min, and start pulling the tape straight at 180° with the tensile testing machine. Read the bonding force of the tape when it is stretched, export the data and divide it by the width of the tape to get the bonding force between the first coating and the positive current collector.
[0094] Diaphragm resistance test
[0095] The positive electrode sheet was baked at 80°C for 30 minutes, and the portion of the positive current collector surface coated with only the first coating was cut into a test sample with a size of 60mm×80mm. The membrane resistance of the first coating was tested using a membrane resistance meter at a test pressure of 0.4T and a holding time of 10s. The membrane resistance of the positive electrode sheet was tested using a membrane resistance meter at a test pressure of 0.4T and a holding time of 10s. The portion of the positive current collector surface coated with the first coating and the positive electrode material layer was cut into a test sample with a size of 60mm×80mm. The membrane resistance of the positive electrode sheet was tested using a membrane resistance meter at a test pressure of 0.4T and a holding time of 10s.
[0096] Infrared spectrum test
[0097] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the positive electrode plate. The positive electrode plate was cleaned with dimethyl carbonate (DMC) for 10 minutes, and then the positive electrode plate was baked at 100°C for 2 hours for standby use. The positive electrode material layer on the positive electrode plate was scraped off to obtain a positive current collector with a first coating on the surface. The infrared spectrum of the positive current collector coated with the first coating was tested using an infrared spectrometer (model Nicolet iS50) and a potassium bromide (KBr) tablet method.
[0098] Example 1
[0099] <Preparation of positive electrode sheet>
[0100] The inorganic nano-boehmite particles (BG-611, provided by Anhui Yishitong Materials Technology Co., Ltd.) were ball-milled, and then the inorganic nano-boehmite particles (Dv50 of 200nm, Dv90 of 600nm), the second binder sodium polyacrylate, the first binder aluminum dihydrogen phosphate and the first conductive agent conductive carbon black were mixed in a mass ratio of 82:9:6:3, deionized water was added as a solvent, and the mixture was stirred evenly to obtain a first coating slurry with a solid content of 75wt%, which was coated on one surface of an 8μm positive electrode current collector aluminum foil, and baked at 120°C for 2 hours to obtain a first coating with a thickness of 0.95μm. The positive electrode active material lithium cobalt oxide, the second conductive agent carbon nanotube (CNT), and the third binder polyvinylidene fluoride were mixed in a mass ratio of 97.3:1.1:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred evenly in a vacuum mixer to obtain a positive electrode material layer slurry with a solid content of 75wt%. The positive electrode material layer slurry is evenly coated on the surface of the first coating layer and dried at 120°C to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on one side. The single-side coating weight of the positive electrode material layer is 267.8 mg / 1540 mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with the first coating layer and the positive electrode material layer coated on both sides. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 80μm, and the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is 84.2.
[0101] <Preparation of negative electrode sheet>
[0102] The negative electrode active material artificial graphite, the fourth binder styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed at a mass ratio of 97.7:1:1.3, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70wt%. The negative electrode slurry was obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The single-sided coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 85μm.
[0103] <Preparation of Electrolyte>
[0104] In an argon atmosphere glove box with a water content of less than 10ppm, carbonate compounds ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 10:30:60 to obtain a basic solvent, and lithium salt LiPF6 was added and stirred evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the basic solvent.
[0105] <Isolation film>
[0106] A polyethylene porous polymer film with a thickness of 8 μm (manufacturer: Celgard Membrane Co., Ltd., USA) was used as a separator.
[0107] <Preparation of lithium-ion batteries>
[0108] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound up, the electrode assembly is packed into an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, the prepared electrolyte is injected, and the lithium-ion battery is obtained through vacuum packaging, standing, forming, and shaping processes, wherein the upper limit voltage of the formation is 4.53V, the formation temperature is 85°C, and the formation time is 45min to 60min.
[0109] Example 2 to Example 23
[0110] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1. The particle size of the inorganic particles is regulated by adjusting the ball milling time of the inorganic particles, and the thickness of the first coating layer is regulated by adjusting the single-sided coating weight of the first coating layer.
[0111] Embodiment 24
[0112] The process is the same as that of Example 1 except that nano-boehmite (BG-613, provided by Anhui Yishitong Materials Technology Co., Ltd.) is used as inorganic particles after ball milling in the process of <Preparation of Positive Electrode Plate>.
[0113] Example 25 to Example 31
[0114] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1. Among them, the thickness of the first coating layer is regulated by adjusting the single-sided coating weight of the first coating layer, the thickness of the positive electrode material layer is regulated by adjusting the single-sided coating weight of the positive electrode material layer, and the particle size of the inorganic particles is regulated by adjusting the ball milling time of the inorganic particles.
[0115] Comparative Examples 1 to 5
[0116] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1. The particle size of the inorganic particles is regulated by adjusting the ball milling time of the inorganic particles, and the thickness of the first coating layer is regulated by adjusting the single-sided coating weight of the first coating layer.
[0117] Comparative Example 6
[0118] Except that the following preparation method is used for <Preparation of the positive electrode sheet>, the rest is the same as Example 1.
[0119] <Preparation of positive electrode sheet>
[0120] The positive electrode active material lithium cobalt oxide, the second conductive agent carbon nanotube (CNT), and the third binder polyvinylidene fluoride were mixed in a mass ratio of 97.3:1.1:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the vacuum mixer was stirred to obtain a positive electrode material layer slurry with a solid content of 75wt%. The positive electrode material layer slurry was evenly coated on one surface of an 8μm positive electrode current collector aluminum foil, and dried at 120°C to obtain a positive electrode sheet coated with a single-sided positive electrode material layer. The single-sided coating weight of the positive electrode material layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet coated with a positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 80μm.
[0121] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.
[0122] Table 1
[0123] Note: “\” in Table 1 means there is no corresponding parameter.
[0124] It can be seen from Examples 1 to 31 and Comparative Examples 1 to 6 that when the positive electrode sheet has the first coating structure of the present application, the membrane resistance of the first coating is high, which can provide a higher safety resistance when the lithium-ion battery is accidentally short-circuited; the membrane resistance of the positive electrode sheet is low, which can improve the conductivity of the positive electrode sheet as a whole; the bonding force between the first coating and the positive electrode collector is high, which can reduce the possibility of internal short circuit during the nail penetration of the lithium-ion battery. The number of cycles of the obtained lithium-ion battery at 45°C until the capacity retention rate is 80% is high, and the pass rate of the nail penetration test is high, so the lithium-ion battery of the present application has good cycle performance and safety performance.
[0125] The thickness of the first coating layer usually affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1 to 6 and Comparative Examples 1 to 2 that when the thickness of the first coating layer is within the scope of this application, the number of cycles of the obtained lithium-ion battery at 45°C until the capacity retention rate is 80% is high, and the pass rate of the nail penetration test is high, indicating that the cycle performance and safety performance of the lithium-ion battery of this application are good. However, the thickness of the first coating layer of Comparative Example 1 is less than the scope of this application, and the pass rate of the lithium-ion battery nail penetration test is low, indicating that its safety performance is poor; the thickness of the first coating layer of Comparative Example 2 is greater than the scope of this application, the membrane resistance of the positive electrode sheet is high, and the number of cycles of the lithium-ion battery at 45°C until the capacity retention rate is 80% is low, indicating that the cycle performance of the lithium-ion battery is poor, and its energy density is also low, and the lithium-ion battery cannot have good cycle performance and safety performance at the same time.
[0126] The Dv50 of inorganic particles usually affects the cycle performance and safety performance of lithium-ion batteries. It can be seen from Example 1, Example 7 to Example 10 and Comparative Examples 3 to Comparative Examples 4 that when the Dv50 of the inorganic particles is within the scope of this application, the number of cycles of the obtained lithium-ion battery at 45°C until the capacity retention rate is 80% is high, and the pass rate of the nail penetration test is high, indicating that the cycle performance and safety performance of the lithium-ion battery of this application are good. However, the Dv50 of the inorganic particles in Comparative Example 3 is less than the scope of this application, the membrane resistance of the positive electrode sheet is high, and the number of cycles of the lithium-ion battery at 45°C until the capacity retention rate is 80% is low, indicating that the cycle performance of the lithium-ion battery is poor; the Dv50 of the inorganic particles in Comparative Example 4 is greater than the scope of this application, the bonding force between the first coating and the positive current collector is low, and the pass rate of the lithium-ion battery nail penetration test is low, indicating that the safety performance of the lithium-ion battery is poor, and the lithium-ion battery cannot have good cycle performance and safety performance at the same time.
[0127] It can be seen from Examples 1, 11 to 31 that when the type and mass percentage of the inorganic particles, the type and mass percentage of the first binder and the glass transition temperature, the type and mass percentage of the second binder, the type and mass percentage of the first conductive agent, the Dv90 of the inorganic particles, and the ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer are within the scope of the present application, and the first coating layer is 3200°C, the thickness of the positive electrode material layer is 100°C, and the thickness of the first coating layer is 200°C. -1 cm to 3400cm -1 When the infrared spectrum has a characteristic peak, the obtained lithium-ion battery has a high number of cycles at 45°C until the capacity retention rate is 80%, and the pass rate of the nail penetration test is high, so the lithium-ion battery of the present application has good cycle performance and safety performance.
[0128] Figure 2 This is the infrared spectrum test chart of the first coating of Example 1 of the present application, Figure 3 This is the infrared spectrum test chart of the first coating of Example 24 of the present application. Figure 2 It can be seen that the infrared spectrum of the first coating of Example 1 is at 3200 cm -1 Up to 3400cm -1 There are characteristic peaks between (shown by the dotted ellipse), indicating that there are hydroxyl functional groups on the surface of the inorganic particles of the first coating. Figure 3 It can be seen that the infrared spectrum of the first coating of Example 24 is at 3200 cm -1 Up to 3400cm -1 There is no characteristic peak between the two, indicating that there is no hydroxyl functional group on the surface of the inorganic particles of the first coating.
[0129] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0130] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0131] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
Claims
1. A positive electrode plate, comprising a positive electrode collector, a first coating and a positive electrode material layer, wherein the first coating is arranged on the surface of the positive electrode collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode collector, the first coating comprises inorganic particles and a first binder, the Dv50 of the inorganic particles is 50nm to 500nm, and the thickness of the first coating is 0.2μm to 2μm.
2. The positive electrode sheet according to claim 1, wherein: The first coating layer has a thickness of 0.2 μm to 0.95 μm.
3. The positive electrode sheet according to claim 1, wherein: The Dv50 of the inorganic particles is 50 nm to 200 nm.
4. The positive electrode sheet according to claim 1, wherein: The Dv90 of the inorganic particles is 400nm to 800nm.
5. The positive electrode sheet according to claim 1, wherein: The ratio of the thickness of the positive electrode material layer to the thickness of the first coating layer is 35 to 450.
6. The positive electrode sheet according to claim 1 or 2, wherein: The inorganic particles include at least one of nano-boehmite or aluminum oxide; based on the mass of the first coating, the mass percentage of the inorganic particles is 80% to 89.5%.
7. The positive electrode sheet according to claim 1 or 2, wherein: The first binder includes at least one of aluminum dihydrogen phosphate, potassium dihydrogen phosphate or sodium dihydrogen phosphate; based on the mass of the first coating, the mass percentage of the first binder is 5% to 10%.
8. The positive electrode sheet according to claim 1, wherein: The first binder has a glass transition temperature of 90°C to 180°C.
9. The positive electrode sheet according to claim 1, wherein: The bonding force between the first coating layer and the positive electrode current collector is 600 N / m to 2000 N / m.
10. The positive electrode sheet according to claim 1, wherein: The first coating also includes a second binder, which includes a water-soluble metal salt compound; based on the mass of the first coating, the mass percentage of the second binder is 5% to 10%.
11. The positive electrode sheet according to claim 10, wherein: The water-soluble metal salt compound includes alkali metal polyacrylate and / or alkaline earth metal polyacrylate, the alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate, and the alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate.
12. The positive electrode sheet according to claim 1, wherein: The first coating also includes a first conductive agent, which includes at least one of conductive carbon black, carbon nanotubes, graphene or carbon nanofibers; based on the mass of the first coating, the mass percentage of the first conductive agent is 0.5% to 5%.
13. The positive electrode sheet according to claim 1, wherein: The infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 There are characteristic peaks between them.
14. The positive electrode sheet according to claim 1, wherein: The diaphragm resistance of the first coating layer is R1, the diaphragm resistance of the positive electrode plate is R2, 5Ω≤R1≤200Ω, 0.5Ω≤R2≤7Ω. 15 . An electrochemical device, comprising the positive electrode sheet according to claim 1 .
16. An electronic device comprising the electrochemical device according to claim 15.
Citation Information
Patent Citations
Positive pole piece, secondary battery and electric device
CN115986130A
Electrochemical device and electronic device
CN116111037A
Positive pole piece, secondary battery and electric device
CN116864610A
Compound as well as preparation method and application thereof
CN119039341A
Positive pole piece, electrochemical device and electronic device
CN119275395A
Cited By
Safe silicon-carbon negative electrode lithium ion battery and preparation method thereof
CN121097176A
Positive electrode sheet, electrochemical device, and electronic device
WO2026149258A1